Automation in the Public Sector: Efficiency at the Expense of Equity?. (2nd January 2019) - Borry, Erin L.; Getha-Taylor, Heather
Abstract : Automation promises to reshape a variety of work contexts in the coming years and the public sector will not be immune. While technology broadly—and automation in particular—offers a range of potential benefits from standardization to operational efficiency to financial savings, the potential tradeoffs and ethical impacts should not be neglected. This article addresses potential implications of automation as they apply to the public-sector workforce and its expressed values. Using data on state and local government employee demographics and occupations, this article utilizes scholarly predictions to forecast the ways in which automation may impact the public workforce, including the sector's commitment to equity goals such as equal employment opportunity and the cultivation of a diverse workforce. Based on this analysis, recommendations are offered for prioritizing these public service values in a swiftly changing context.